2011
DOI: 10.1007/s00056-011-0013-8
|View full text |Cite
|
Sign up to set email alerts
|

Patient Expectations, Acceptance and Preferences in Treatment with Orthodontic Mini-implants

Abstract: Patients tolerated the various insertion procedures equally well. However, there were differences with regard to the injection technique: The patients favored an injection immediately next to the mini-implant insertion area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 48 publications
(112 reference statements)
1
27
0
2
Order By: Relevance
“…Nor are there any studies evaluating patients' subjective preference concerning local anesthetics. Our substudy I already demonstrated that it is the injection itself that causes more pain than the actual surgery [28]. The results of the present study -that no local anesthesia is needed when removing mini-implants -support that hypothesis.…”
Section: Diskussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Nor are there any studies evaluating patients' subjective preference concerning local anesthetics. Our substudy I already demonstrated that it is the injection itself that causes more pain than the actual surgery [28]. The results of the present study -that no local anesthesia is needed when removing mini-implants -support that hypothesis.…”
Section: Diskussionsupporting
confidence: 80%
“…The patients in this study were recruited from substudy I [28] and consisted of 30 patients randomly selected from the study group. The mean age was 15.03 years (± 0.83).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the variety of screw types and their usage, only a few general conclusions can be drawn for the experience of pain and discomfort related to the use of miniscrews. 3 Lehnen et al 4 showed that the drilling of a pilot hole was reported to be as uncomfortable as the pressure that self-drilling screws cause in the bone, and when treatment includes flap surgery or soft tissue punching, patients report even higher pain levels. 5,6 Lee et al 7 showed in a cohort study that patients expect the buccal placement of miniscrews to be more painful than it finally is.…”
Section: Introductionmentioning
confidence: 98%